FACTORS AFFECTING STOCK RETURNS IN BANKS LISTED ON KBMI 4 INDONESIA STOCK EXCHANGE (IDX) PERIOD 2015 – 2024 - Jasmine, Gadis Muthia; Kaligis, Villy Frisillia; Muchtar, Susy (Distribusi - Journal of Management and Business, 2025)
This research provides an original contribution by analyzing the impact of cash flows, dividends, firm size, and the effects of the Covid-19 pandemic on stock returns for KBMI IV banks listed on the Indonesia Stock Exchange (IDX) during the period of 2015–2024. This approach is rarely examined simultaneously in the context of Indonesian banking, thus offering a new perspective in the existing literature. The primary objective of this study is to evaluate whether the variables of operating cash flow, investing cash flow, financing cash flow, dividends, firm size, and Covid-19 have a significant effect on stock returns. The methodology employed is a quantitative approach utilizing secondary data from the annual financial statements of KBMI IV banks, analyzed through multiple linear regression methods based on panel data with the aid of EViews 12 software and the Ordinary Least Squares (OLS) approach. Empirical results indicate that the regression model applied is significant simultaneously (F-test), with an adjusted R² of 51.75%, indicating that the six independent variables can explain more than half of the variation in stock returns. Partially, variables such as investing cash flow and Covid-19 have been shown to have a positive and significant impact on stock returns, while financing cash flow, dividends, and firm size exhibit insignificant results. The implications of this research emphasize the importance of cash flow management and effective communication strategies during crises, such as a pandemic, to maintain investor confidence. These findings provide a solid foundation for bank managers and investors in making strategic decisions and investments based on fundamental banking factors.